Preparation method and application of nano silicon / silicon carbide composite material

By introducing silicon source and carbon source into hydrogen-thermal plasma, synchronous in-situ growth of nanosilicon/silicon carbide composite materials is solved, and the problems of excessive silicon carbide and insufficient interface binding force in traditional materials are obtained, and high-performance nanosilicon/silicon carbide composite materials are obtained.

CN119735208APending Publication Date: 2025-04-01HENAN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411862139.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In traditional nano-silicon/silicon carbide anode materials, excessive silicon carbide affects the embedding of lithium ions, and the interface binding force is weak, resulting in loss of electrochemical activity and degradation of performance.

Method used

By introducing a silicon source and a carbon source into a hydrogen-heated plasma, it reacts at high temperature to form a nano-silicon/silicon carbide composite material, achieving synchronous in-situ growth of silicon carbide and nano-silicon to form a composite material with strong bond connection.

Benefits of technology

The obtained nanosilicon/silicon carbide composite material has high interfacial bonding strength, which can remain stable during volume expansion, improving structural stability and electrochemical properties, including conductivity, power properties and cyclic stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735208A_ABST
    Figure CN119735208A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of lithium ion negative electrode materials, and discloses a preparation method of a nano silicon / silicon carbide composite material, which comprises the following steps: introducing a silicon source and a carbon source into hydrogen thermal plasma, quickly gasifying and cracking the silicon source into silicon steam, quickly gasifying and cracking the carbon source into carbon steam, and carrying out heat treatment to obtain the nano silicon / silicon carbide composite material. And reacting the silicon vapor with the carbon vapor to generate the nano silicon / silicon carbide composite negative electrode material. According to the method, a silicon source and a carbon source are used as raw materials, the characteristics of high temperature and instantaneous cooling of hot plasma are utilized, carbon source gas is introduced in the process of preparing nano silicon, the growth process of the nano silicon is regulated and controlled, silicon carbide and the nano silicon are enabled to grow synchronously in situ, and one-step preparation of the nano silicon / silicon carbide composite material with the interpenetrating structure is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion negative electrode material preparation, and relates to a preparation method and application of a nano silicon / silicon carbide composite material. Background Art

[0002] Lithium-ion batteries are one of the most excellent battery systems, with advantages such as high voltage, high specific energy, low weight, low volume, and long life. However, the specific capacity of graphite negative electrode materials for traditional lithium-ion batteries is close to its theoretical value (-372 mAh / g), which is difficult to meet market demand. Therefore, it has become an urgent need to develop a new negative electrode material with high energy density, high power density, high safety and low cost.

[0003] Compared with graphite materials, silicon anode is considered to be one of the most promising next-generation anode materials due to its high specific capacity (3579mAh / g) and low lithium insertion potential (~0.2V). However, silicon has poor electrical conductivity and is accompanied by a huge volume change (~300%) during lithium insertion and extraction. The huge volume change will cause material pulverization, electrode shedding, repeated growth of SEI film, etc., affecting capacity and cycle efficiency, severely limiting its practical application.

[0004] Silicon carbide has attracted much attention as a new type of silicon-based negative electrode material, and has great potential due to its high specific capacity and excellent chemical stability. Silicon / silicon carbide composite negative electrode materials combine the high lithium storage capacity of silicon and the stability of silicon carbide, making them have both high energy density and good structural stability during charging and discharging. Nano-silicon / silicon carbide negative electrode materials have a low expansion rate, which helps to reduce the problems of battery capacity reduction and structural damage caused by volume expansion, making them show good cycle stability and fast charging capabilities.

[0005] Patent CN118782779A discloses a method for preparing a silicon carbide negative electrode material, comprising mixing a polydimethylsiloxane prepolymer and a single-walled carbon nanotube slurry; adding a curing agent and curing in a vacuum oven to remove bubbles; reacting the obtained cross-linked polymer in a high temperature vacuum to obtain a polycarbosilane melt; and melt-spinning, sintering, and granulating the polycarbosilane melt in an inert atmosphere to obtain silicon carbide particles.

[0006] Patent CN117976901A discloses a method for preparing a modified silicon carbide negative electrode active material, comprising mixing an organic compound containing an M element, a silicon-based compound containing a polymerizable group and a solvent, and performing a polymerization reaction to obtain a modified polymer precursor; and heat-treating the modified polymer precursor to obtain the modified silicon carbide negative electrode active material.

[0007] Duc Tung Ngo et al. reported a synthesis method of Si@SiC material in Applied Materials & Interfaces, Vol. 9, 2017, pp. 32790–32800. First, SiO2 was dispersed in a certain amount of 2% PVP aqueous solution to form a uniform suspension. Next, the sample was mixed evenly with Mg powder, placed in a stainless steel crucible, and then heated to prepare Si@SiC with different SiC contents. In a vertical tube furnace, it was heated in an Ar atmosphere for 1 h. After the chemical reaction was completed, the furnace was naturally cooled to room temperature. The prepared sample was then washed with 2M HCl and 0.1M HF solutions, and the obtained sample was then rinsed with ethanol and then dried under vacuum to obtain Si@SiC material.

[0008] However, traditional nano-silicon / silicon carbide negative electrode materials have the following two problems: First, silicon carbide is a covalently bonded compound with a strong lattice bond. Too thick silicon carbide will affect the embedding of lithium ions into silicon, resulting in a loss of electrochemical activity. Second, the contact interface between silicon and silicon carbide does not form a strong chemical bond or physical adsorption, resulting in weak bonding at the interface. Intact interfacial bonding will increase the interfacial resistance inside the composite material, which will affect the transmission efficiency of electrons in the material, thereby causing a significant decrease in the electrochemical performance of the composite material. Therefore, there is an urgent need for a method that can in situ prepare nano-silicon / silicon carbide composite battery negative electrode materials with high electrochemical activity and high interfacial bonding strength. Summary of the invention

[0009] The present invention aims to solve the technical problems that the presence of too thick silicon carbide in a nano-silicon / silicon carbide composite material will affect the embedding of lithium ions into silicon, resulting in loss of electrochemical activity, and the weak bonding force at the interface will lead to poor performance of lithium-ion batteries. A method for preparing a nano-silicon / silicon carbide composite material is provided.

[0010] To achieve the above object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a nano-silicon / silicon carbide composite material, comprising the following steps:

[0012] Silicon source and carbon source are introduced into hydrogen thermal plasma, the silicon source is rapidly gasified and cracked into silicon vapor, the carbon source is rapidly gasified and cracked into carbon vapor, and then the silicon vapor and carbon vapor react to form nano-silicon / silicon carbide composite negative electrode material.

[0013] In the above technical solution, the method for preparing hydrogen thermal plasma includes the following steps: using a thermal plasma generator to generate stable argon thermal plasma; adding hydrogen to one or a combination of central gas, side gas or quenching gas to generate stable hydrogen thermal plasma.

[0014] In the above technical solution, the hydrogen is added at a position above, in or below the argon thermal plasma arc, or a combination thereof.

[0015] In the above technical solution, the amount of hydrogen added is 1 to 4000 L / h.

[0016] In the above technical solution, the amount of hydrogen added is 100 to 2000 L / h.

[0017] In the above technical solution, the silicon source is one or a combination of metallurgical silicon, silicon tetrahydride, monochlorosilane, dichlorosilane, trichlorosilane or silicon tetrachloride.

[0018] In the above technical solution, the carbon source is one or a combination of styrene, methane and acetylene.

[0019] In the above technical scheme, the methods of introducing the silicon source and the carbon source include: ① the silicon source and the carbon source are pre-mixed and then enter the hydrogen thermal plasma arc together; ② only the silicon source enters the hydrogen thermal plasma arc, and the carbon source enters under the hydrogen thermal plasma arc; ③ only the carbon source enters the hydrogen thermal plasma arc, and the silicon source enters under the hydrogen thermal plasma arc.

[0020] In the above technical solution, the silicon / carbon molar ratio of the silicon source and the carbon source is 1:0.1-100, preferably 1:1-60.

[0021] In a second aspect, the present invention also provides the use of the nano-silicon / silicon carbide composite material prepared by the above preparation method in the negative electrode material of a lithium-ion battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses silicon source and carbon source as raw materials, utilizes the high temperature and instantaneous cooling characteristics of thermal plasma, introduces carbon source gas in the process of preparing nano-silicon, regulates the growth process of nano-silicon and makes silicon carbide and nano-silicon grow synchronously in situ, thereby realizing a one-step preparation of nano-silicon / silicon carbide composite materials.

[0024] The nano-silicon / silicon carbide composite negative electrode material obtained by the present invention is a synchronous in-situ generation of silicon carbide and nano-silicon. The two are connected by a strong chemical bond and have a high interface bonding strength. They can remain stable during repeated volume expansions, and are a key measure to buffer volume changes and improve structural stability. In addition, silicon carbide and nano-silicon are evenly distributed, and the two are interpenetrating structures. Silicon carbide will not affect the embedding of lithium ions into silicon. Finally, silicon carbide has a strong ability to adsorb fluoroethylene carbonate molecules and can stabilize the solid electrolyte membrane. Therefore, compared with the traditional single silicon negative electrode and silicon carbide negative electrode, the nano-silicon / silicon carbide composite negative electrode material obtained by the present invention has good electrical conductivity, power performance, electrochemical activity and cycle stability. In summary, the present invention can provide a new strategy for the surface and interface design of nano-silicon / silicon carbide composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope (SEM) photograph of the nano-silicon / silicon carbide composite material obtained in Example 9.

[0026] Figure 2 This is a transmission electron microscope (TEM) photograph of the nano-silicon / silicon carbide composite material obtained in Example 9.

[0027] Figure 3 This is the X-ray diffraction (XRD) spectrum of the nano-silicon / silicon carbide composite material obtained in Example 9.

[0028] Figure 4 The battery cycle data of the nano-silicon / silicon carbide composite material obtained in Example 9 at a current density of 200 mA / g. DETAILED DESCRIPTION

[0029] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. The test methods in the following examples are conventional methods unless otherwise specified.

[0030] The thermal plasma generator used in the following examples is a radio frequency inductively coupled thermal plasma with a power of 36Kw:

[0031] Example 1

[0032] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0033] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 200 L / h; hydrogen is added to the quenching gas at a rate of 800 L / h. Stable hydrogen thermal plasma is generated.

[0034] 2) Preparation of nano-silicon / silicon carbide composite materials: Pre-mixed silicon tetrachloride and methane are introduced into hydrogen thermal plasma, with a silicon / carbon molar ratio of 1:5. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0035] Example 2

[0036] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0037] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 200 L / h; hydrogen is added to the quenching gas at a rate of 800 L / h. Stable hydrogen thermal plasma is generated.

[0038] 2) Preparation of nano-silicon / silicon carbide composite materials: Pre-mixed silicon tetrachloride and methane are introduced into hydrogen thermal plasma, with a silicon / carbon molar ratio of 1:10. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0039] Example 3

[0040] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0041] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 200 L / h; hydrogen is added to the quenching gas at a rate of 800 L / h. Stable hydrogen thermal plasma is generated.

[0042] 2) Preparation of nano-silicon / silicon carbide composite materials: Pre-mixed silicon tetrachloride and methane are introduced into hydrogen thermal plasma, with a silicon / carbon molar ratio of 8:1. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0043] Example 4

[0044] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0045] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1200 L / h. Stable hydrogen thermal plasma is generated.

[0046] 2) Preparation of nano-silicon / silicon carbide composite materials: Only silicon tetrachloride is introduced into hydrogen thermal plasma, and methane enters under the arc. The silicon / carbon molar ratio is 1:3. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0047] Example 5

[0048] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0049] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1200 L / h. Stable hydrogen thermal plasma is generated.

[0050] 2) Preparation of nano-silicon / silicon carbide composite materials: Only silicon tetrachloride is introduced into hydrogen thermal plasma, and methane enters under the arc. The silicon / carbon molar ratio is 1:8. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0051] Example 6

[0052] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0053] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1200 L / h. Stable hydrogen thermal plasma is generated.

[0054] 2) Preparation of nano-silicon / silicon carbide composite materials: Only silicon tetrachloride is introduced into hydrogen thermal plasma, and methane enters under the arc. The silicon / carbon molar ratio is 10:1. Silicon tetrachloride is rapidly gasified and cracked into silicon vapor, and methane is rapidly gasified and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0055] Example 7

[0056] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0057] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1600 L / h. Stable hydrogen thermal plasma is generated.

[0058] 2) Preparation of nano-silicon / silicon carbide composite materials: Only methane is introduced into hydrogen thermal plasma, and silicon tetrachloride enters under the arc, with a silicon / carbon molar ratio of 1:1. Silicon tetrachloride is rapidly vaporized and cracked into silicon vapor, and methane is rapidly vaporized and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0059] Example 8

[0060] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0061] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1600 L / h. Stable hydrogen thermal plasma is generated.

[0062] 2) Preparation of nano-silicon / silicon carbide composite materials: Only methane is introduced into hydrogen thermal plasma, and silicon tetrachloride enters under the arc. The silicon / carbon molar ratio is 1:7. Silicon tetrachloride is rapidly vaporized and cracked into silicon vapor, and methane is rapidly vaporized and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0063] Example 9

[0064] The preparation method of the nano-silicon / silicon carbide composite material in this embodiment specifically includes the following steps:

[0065] 1) Generate stable hydrogen thermal plasma: The thermal plasma generator generates stable argon thermal plasma. Hydrogen is added to the edge gas at a rate of 250 L / h; hydrogen is added to the quenching gas at a rate of 1600 L / h. Stable hydrogen thermal plasma is generated.

[0066] 2) Preparation of nano-silicon / silicon carbide composite materials: Only methane is introduced into hydrogen thermal plasma, and silicon tetrachloride enters under the arc. The silicon / carbon molar ratio is 3:1. Silicon tetrachloride is rapidly vaporized and cracked into silicon vapor, and methane is rapidly vaporized and cracked into carbon vapor. Subsequently, the silicon vapor and carbon vapor react to form a nano-silicon / silicon carbide composite material.

[0067] The morphology of the nano-silicon / silicon carbide composite material obtained in Example 9 was examined using a Japanese electron scanning electron microscope (JSM-7001F). The results are as follows: Figure 1 As shown, the prepared nano-silicon / silicon carbide composite material is spherical particles with a smooth surface and uniform particle size.

[0068] The structure of the nano-silicon / silicon carbide composite material obtained in Example 9 was examined using a Japanese electron transmission electron microscope (JEM-21001F). The results are as follows: Figure 2 As shown, the prepared nano-silicon / silicon carbide composite material is a spherical particle with a dense interior. Si and SiC are interpenetrating structures, the two are closely connected, there is no crack, and has a high interface bonding strength.

[0069] The composition of the nano-silicon / silicon carbide composite material obtained in Example 9 was detected by Philips X-ray powder diffractometer (X'Pert PRO MPD). The results are as follows: Figure 3 As shown, in XRD, there are both diffraction peaks belonging to Si and diffraction peaks belonging to SiC.

[0070] The content of silicon carbide in the nano-silicon / silicon carbide composite materials obtained in Examples 1 to 9 was detected using a carbon-sulfur analyzer (Lico CS844). The results are shown in Table 1. The content of SiC is positively correlated with the amount of carbon added.

[0071] Electrochemical performance characterization: The nano-silicon / silicon carbide composite material prepared in Examples 1 to 9, acetylene black, and CMCLi-A (binder) were mixed in a mass ratio of 6:2:2 to form a slurry, and evenly coated on a copper foil current collector to obtain an electrode sheet. Metal lithium was used as a counter electrode, a polypropylene microporous membrane was used as a diaphragm, and 1 mol / L LiPF6 (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1) was used as an electrolyte. A button cell was assembled in an argon-protected glove box, and a charge and discharge test was performed. The test current density was 200 mA / g, and the charge and discharge voltage range was 0.01-3.0 V. The test results are shown in Table 1.

[0072] The results of the battery of Example 1 after 300 cycles at a current density of 200 mA / g are as follows: Figure 4 As shown in the figure, it can be seen that the Si / SiC composite material has excellent cycle stability and still has a reversible capacity retention rate of 80.3% after 300 cycles without further carbon coating.

[0073] Table 1 Battery performance test results

[0074]

[0075]

[0076] As can be seen from Table 1, by controlling the silicon / carbon molar ratio of the silicon source and the carbon source and the mixing method of the silicon source and the carbon source, nano silicon / silicon carbide composite materials with different properties can be prepared. Its discharge specific capacity and first coulomb efficiency are related to the feed ratio and the mixing method of the silicon source and the carbon source. Excellent electrochemical performance can be obtained by using different feed ratios of silicon source and carbon source and mixing methods, which shows that the technology has good effect and strong scalability. In addition, compared with the prior art, the method is simple in steps, low in cost and easy to apply.

[0077] The embodiments described above are only preferred embodiments of the present invention and are only used to explain the present invention, not to limit the scope of implementation of the present invention. For those skilled in the art, other implementation methods can certainly be easily made by replacement or modification based on the technical contents disclosed in this specification. Therefore, all changes and improvements made on the principles of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A method for preparing a nano-silicon / silicon carbide composite material, characterized in that: The following steps are involved: Silicon source and carbon source are introduced into hydrogen thermal plasma, the silicon source is rapidly gasified and cracked into silicon vapor, the carbon source is rapidly gasified and cracked into carbon vapor, and then the silicon vapor and carbon vapor react to form nano-silicon / silicon carbide composite negative electrode material.

2. The preparation method according to claim 1, characterized in that: The preparation method of hydrogen thermal plasma comprises the following steps: generating stable argon thermal plasma by using a thermal plasma generating device; adding hydrogen to one or a combination of central gas, side gas or quenching gas to generate stable hydrogen thermal plasma.

3. The preparation method according to claim 2, characterized in that: The hydrogen is added at a position above, in or below the argon thermal plasma arc, or a combination thereof.

4. The preparation method according to claim 2 or 3, characterized in that: The amount of hydrogen added is 1-4000 L / h.

5. The preparation method according to claim 2 or 3, characterized in that: The amount of hydrogen added is 100~2000 L / h.

6. The preparation method according to claim 1, characterized in that: The silicon source is one or a combination of metallurgical silicon, silicon tetrahydride, monochlorosilane, dichlorosilane, trichlorosilane or silicon tetrachloride.

7. The preparation method according to claim 1, characterized in that: The carbon source is one or a combination of styrene, methane and acetylene.

8. The preparation method according to claim 1, characterized in that: The introduction methods of the silicon source and the carbon source include: ① the silicon source and the carbon source are pre-mixed and then enter the hydrogen thermal plasma arc together; ② only the silicon source enters the hydrogen thermal plasma arc, and the carbon source enters under the hydrogen thermal plasma arc; ③ only the carbon source enters the hydrogen thermal plasma arc, and the silicon source enters under the hydrogen thermal plasma arc.

9. The preparation method according to claim 1, characterized in that: The silicon / carbon molar ratio of the silicon source and the carbon source is 1:0.1-100.

10. Use of the nano-silicon / silicon carbide composite material prepared by the preparation method according to any one of claims 1 to 9 as a negative electrode material for lithium-ion batteries.

Citation Information

Cited By

  • Superfine silicon-carbon composite material based on in-situ electrochemical induction and preparation method and application thereof

    CN120565654A

  • Double-layer nano silicon-based material as well as preparation method and application thereof

    CN121097060A